Developing English Reading Materials for Eight Grade of Islamic Junior High School Jambi - Anggraini, Roza; Saharudin; Wachyunni, Sri (SAFE-Network, 2025)
This research aimed to develop English reading materials as supplementary resources for eighth-grade students at an Islamic junior high school in Jambi. Utilizing the ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation stages the study followed a research and development approach. Data were gathered through expert validations, teacher evaluations, and student try-outs using both qualitative and quantitative methods. The material expert scored the product at 75%, suggesting content restructuring, while the media expert rated it at 94.44%, recommending visual improvements. The one-to-one teacher trial resulted in a 94.64% score, emphasizing pedagogical clarity and linguistic accuracy. Finally, student responses during the small group trial indicated a 90.8% satisfaction level, reflecting positive user engagement. The results confirm the worksheet's validity and effectiveness in enhancing reading skills, making it a relevant and implementable instructional tool in English language learning contexts.